(untitled) (Comparative Professional Pedagogy, 2023)
The article studies the structure of future lawyers’ training at British universities. It is stated that the path to the legal profession in the UK involves three main stages of training: an academic study programme, a professional training programme and an internship. It is established that the academic stage is usually implemented at the level of bachelor’s and master’s degree programmes and involves obtaining a "qualified" law degree. A "qualified law degree" in the context of legal education in the UK refers to a programme which meets the necessary criteria for a student to proceed to the next stage of legal training. The programme must also be recognized by the legal professional bodies responsible for the regulation and supervision of solicitors and barristers. It is established that students who successfully obtain a qualified law degree are entitled to proceed to the practical stage of legal education. The requirements for the professional training programmes for barristers and solicitors are described. The author analyses the peculiarities of the Legal Practice Course for solicitors and the Bar Professional Training Courses for attorneys-at-law. The programmes provide for students to master the training modules defined by professional regulators, and to develop universal professional knowledge and skills. The author establishes that the final stage of the professional training of future lawyers is a two-year training contract for solicitors and a one-year pupillage for barristers. It is concluded that each subsequent stage of future lawyers’ training complements the previous one, which provides a consistent expansion of the student’s general training and promotes the development of their analytical skills. Besides, it is found out that practicing solicitors and barristers are subject to mandatory post-qualification (continuing) professional development (CPD). Taking into account positive experience of GB in training future lawyers, we consider it necessary to analyze the programs of legal education offered at British universities more thoroughly in order to outline recommendations on how to improve the national system of higher legal education.